The Piecewise Concave Function - Zangwill, Willard I. (Management Science, 1967)
An important function which is neither concave nor convex often arises in production and inventory models. This function is herein called piecewise concave and can be considered to be a generalization of the concave function. Essentially it is the maximum of a collection of concave functions. Various properties of piecewise concave functions are explored in this paper. In particular, a theory is developed to locate the point at which such functions are minimized. A short discussion of applications is included.